Project Management: Achieving Competitive Advantage, Global Edition - Pinto, Jeffrey K (Pearson International Content, 2019)
For project management courses. In its 5th Edition, Project Management: Achieving Competitive Advantage takes a contemporary, decisive, and business-oriented approach to teaching and learning project management. To promote a comprehensive, multi-industry understanding of the text, the author addresses project management theory within the context of a variety of successful organisations, whether they be publicly held, private, or nonprofit. Comprehensive case analysis and detailed exercises, including brand-new, contemporary case studies for the 5th Edition, give students the tools to assess projects in real time, while also leveraging the latest project management technology, including MS Project 2016. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.